PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM PADA PT. SEMEN INDONESIA PERIODE 2012-2017 - Fatichatur Rachmaniyah (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2018)
This research aim to test the influence of profitability which consist of return on asset, return on equity, and earning per share towards stock price of PT. Semen Indonesia neither partial nor simultaneous. The data research period use data quartely financial in 2012 - 2017, with the data type is time series. The data analysis technique by using multiple regressions analysis. The result of research by using F test shows that simultaneously return on asset, return on equity and earning per share has significant positive influence to the stock price. The result of partial test (t test) shows that return on asset, return on equity and earning per share has significant positive influence to the stock price.